Returning Education Research to Teachers: Education Research As Advocacy - Mark Girod; Michael Pardales; Gina Cervetti (Networks: An Online Journal for Teacher Research, 2002)
This article represents the collaborative efforts of three teachers. Each of us is currently enrolled in a doctoral program at a Research I university, struggling with the pressures and stresses of balancing newfound researcher voices with our teacher voices. Although this is collaborative, it is written in the first person as our voices mingle a reflection of our experience. We hope other teachers will find our ideas compelling, resonant with their own, and feel moved to action in the style we suggest. Education research should be the domain of teachers and this is a call for teachers to take back the endeavor.